2018
DOI: 10.1002/jwmg.21602
|View full text |Cite
|
Sign up to set email alerts
|

Statistical dependence for detecting whale‐watching effects on humpback whales

Abstract: Whale-watching is one of the fastest growing ecotourism industries and involves the observation of endangered wild cetacean species. However, this growth has raised concerns because of the negative effects this activity may have on the behavior and survival of focal species. Hence, detecting the effects of this activity requires sensitive analytical methods allowing the implementation of regulations to protect cetacean welfare. We compared the performance of different hypothesis tests from classical and Bayesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 47 publications
0
13
0
4
Order By: Relevance
“…Therefore the surface interval encapsulates one to many surfacing events defined as when the whale breaks the surface of the water to respire. Surfacing events are separated by brief submergences (e.g., Dolphin, 1987;Stelle et al, 2008;Godwin et al, 2016;Garcia-Cegarra et al, 2019). During each surfacing event (surfacing) the whale may provide multiple 'cues' that can be perceived by the mariner to infer the whale's distance from the ship and direction of travel (Hiby and Ward, 1986).…”
Section: Availability Of Whales For Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore the surface interval encapsulates one to many surfacing events defined as when the whale breaks the surface of the water to respire. Surfacing events are separated by brief submergences (e.g., Dolphin, 1987;Stelle et al, 2008;Godwin et al, 2016;Garcia-Cegarra et al, 2019). During each surfacing event (surfacing) the whale may provide multiple 'cues' that can be perceived by the mariner to infer the whale's distance from the ship and direction of travel (Hiby and Ward, 1986).…”
Section: Availability Of Whales For Detectionmentioning
confidence: 99%
“…The availability and detection processes have been well studied owing to its relevance for abundance estimation (via distance sampling), and we refer to these studies for describing factors that influence cue frequency and behavior (Hiby and Ward, 1986;Zerbini et al, 2006). Gray, blue, and humpback whales (among many others) regularly embark on a cycle of surface intervals, consisting of several shallow submergences between respiration/surfacing events, punctuated by longer deep dives (e.g., Dolphin, 1987;Godwin et al, 2016;Garcia-Cegarra et al, 2019). Consequently, whales are infrequently but regularly available to be detected.…”
Section: Availability and Detection Processmentioning
confidence: 99%
“…As whale watching grows, several studies have demonstrated the negative consequences of this activity on the behavior of cetacean species (reviewed in Senigaglia et al, 2016). Effects have been reported for small and large cetacean species including alterations in swimming speed, direction, breathing frequency, and overall behavior (e.g., Noren et al, 2009;Christiansen et al, 2010;Stamation et al, 2010;Senigaglia et al, 2016;García-Cegarra et al, 2019). Studies have linked those behavioral changes into effects on energy budget and metabolism of the species (e.g., Williams et al, 2006;Christiansen et al, 2013Christiansen et al, , 2014a.…”
Section: Introductionmentioning
confidence: 99%
“…The humpback whale is one of the most popular species for whale watching (O'Connor et al, 2009). A suite of negative effects in response to whale-watching boats, such as the alteration of surfacing and diving behavior, aerial activity, acoustic behavior, and swimming speed (e.g., Corkeron, 1995;Scheidat et al, 2004;Sousa-Lima and Clark, 2008;Stamation et al, 2010;García-Cegarra et al, 2019) have been documented on the species. Humpback whales migrate from polar and temperate feeding grounds to tropical and subtropical breeding grounds (Dawbin, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, whales must expend extra energy to avoid boats, while decreasing the occurrence of necessary survival activities (e.g., nursing, foraging, and reproduction; Morete et al, 2007;Stamation et al, 2010;Schaffar et al, 2013;Fournet et al, 2018;Fiori et al, 2019). This is especially true in breeding areas that are primarily frequented by mother and calf groups because they are more susceptible to whale watching disturbances (Morete et al, 2007;García-Cegarra et al, 2019). One study suggested that long-term disruption of routine behaviors caused by high levels of negative boat and whale interactions could have lasting reproductive impacts on humpback whale populations (Braithwaite et al, 2015), while others highlight potential impacts due to the inability for whales to effectively communicate due to "acoustic masking" from loud boat sounds (Rossi-Santos, 2016;Erbe et al, 2018, p. 290).…”
Section: Introductionmentioning
confidence: 99%